Dampak Media Sosial Facebook dan Instagram Terhadap Kunjungan Wisatawan di Desa Wisata Tambakbulusan - Mulyono, Mulyono; Narolita, Mella; Rahman, Abdul; Kusumawati, Vita Ardiana (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of Facebook and Instagram social media on the decision of tourist visits in Tambakbulusan Tourism Village, Demak Regency. The research method used was quantitative descriptive with a survey approach of 175 tourist respondents. Data analysis was carried out using Structural Equation Modeling (SEM) based on SmartPLS 3.0. The results showed that both platforms had a positive and significant influence on tourist visit decisions with a p-value = 0.000. Facebook has a greater influence (β=0.464) than Instagram (β=0.275). These findings confirm that Facebook plays a strong role in building trust and social interaction between travelers through online communities, while Instagram is more influential in shaping the visual image of destinations and emotional appeal. This research reinforces previous findings on the importance of the role of social media in tourism marketing, while also making a new contribution in the context of local destinations. The practical implication of this study is the need for destination managers to integrate promotional strategies across both platforms to optimize tourist interest and visit decisions.